Radial imbibition in paper under temperature differences - Lopez Villa, Abel (2019)
Spontaneous radial imbibition into thin circular samples of porous material when they have been subjected to radial temperature differences was analyzed theoretically and experimentally. The use of the Darcy equation allows us to take into account temperature variations in the dynamic viscosity and surface tension in order to found the one-dimensional equation for the imbibition fronts. Experiments in blotting paper show the good fit between the experimental data to theoretical profiles.